2012
DOI: 10.1007/s10549-012-2019-3
|View full text |Cite
|
Sign up to set email alerts
|

Benign thyroid disease is associated with breast cancer: a meta-analysis

Abstract: The controversial relationship between benign thyroid diseases and breast cancer (BC) has been investigated for over 50 years. Despite extensive population studies, the results as a whole have been inconsistent. The purpose of this study was to collate and analyse available data, calculating a pooled odds ratio (OR) of the risk of BC in patients diagnosed with benign thyroid diseases. Studies were obtained from a database search of MEDLINE, EMBASE, PubMed, Current Contents Connect and Google Scholar with addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 43 publications
1
85
2
5
Order By: Relevance
“…Nevertheless, other studies have demonstrated a higher (8,21,22) or a lower incidence of thyroid disease in BC cases (23). Hashimoto's disease, with or without positive thyroid antibodies (TPO-Abs and Tg-Abs), has been shown to be associated with an increased risk of BC (8,9,(24)(25)(26)(27) and, according to some studies, with a better prognosis and increased disease-free survival in BC cases (16,28). In our study, it seemed that Hashimoto's disease was not associated with BC; however, the small sample size precluded any definitive conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, other studies have demonstrated a higher (8,21,22) or a lower incidence of thyroid disease in BC cases (23). Hashimoto's disease, with or without positive thyroid antibodies (TPO-Abs and Tg-Abs), has been shown to be associated with an increased risk of BC (8,9,(24)(25)(26)(27) and, according to some studies, with a better prognosis and increased disease-free survival in BC cases (16,28). In our study, it seemed that Hashimoto's disease was not associated with BC; however, the small sample size precluded any definitive conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Shering et al (18) and Ito and Maruchi (17) observed that Japanese women with Hashimoto's thyroiditis had a higher incidence of mammary cancer than women without thyroid disease. Two recent meta-analyses showed no significant association, except for autoimmune thyroiditis which increased breast cancer risk; however, the heterogeneity of the studies analyzed precludes firm conclusions (7,22).…”
Section: Discussionmentioning
confidence: 95%
“…A recent meta-analysis has been written with the purpose of collating and analyzing available data from 28 studies, calculating a pooled odd ratio (OR) of the risk of breast cancer in patients diagnosed with benign thyroid diseases. 11 The study demonstrated significant evidence of an increased risk of breast cancer in patients with autoimmune thyroiditis (OR: 2.92, 95%CI: 2.13-4.01). Besides the biological mechanisms reported above, the presence of the sodium-iodide symporter (NIS) in both breast and thyroid tissue led to the hypothesis that the uptake and oxidation of iodine may play a role in the development of breast cancer.…”
mentioning
confidence: 84%